Plasma p‐tau231 in the presenilin 1 E280A autosomal dominant Alzheimer's disease kindred: A cross‐sectional and longitudinal cohort study - Malotaux, Vincent; Ashton, Nicholas J.; Öhrfelt, Annika; Chen, Yinghua; Su, Yi; Garcia‐Ospina, Gloria; Guzman‐Martínez, Claudia; Villegas‐Lanau, Andres; Gómez‐Ramirez, Johana; Giraldo‐Chica, Margarita; Aguillon, David; Tirado, Victoria; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION Plasma phosphorylated tau (p‐tau)‐231 is a promising biomarker for Alzheimer's disease (AD), particularly in preclinical stages. We evaluated its diagnostic value in presenilin 1 (PSEN1) E280A mutation carriers versus non‐carriers and compared it to p‐tau217 and neurofilament light chain (NfL). METHODS We analyzed plasma p‐tau231 in 722 carriers and 640 non‐carriers (ages 18–75). Longitudinal data from 164 carriers and 132 non‐carriers were available, with 137 carriers and 109 non‐carriers having p‐tau231, p‐tau217, and NfL levels. Analyses used linear mixed effects models and restricted cubic splines. RESULTS E280A carriers had higher p‐tau231 levels than non‐carriers (9.0 ± 7.4 vs. 5.2 ± 3.4 pg/mL, P < 0.001). Baseline p‐tau231 levels correlated with age, distinguishing carriers at age 23. Rates of change differed at age 19, ≈ 25 years before cognitive impairment. In a subset, p‐tau231 changes differentiated carriers by age 20, earlier than p‐tau217 and NfL. DISCUSSION Plasma p‐tau231 is a sensitive biomarker for early AD detection and progression monitoring. Highlights Plasma phosphorylated tau (p‐tau)231 levels are associated with age in presenilin 1 carriers and non‐carriers. Baseline p‐tau231 levels diverged between carriers and non‐carriers at age 23. Plasma p‐tau231 changes distinguished carriers by age 19, at very early stages. P‐tau231 longitudinal changes differentiate carriers earlier than p‐tau217 or neurofilament light chain.